(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article deals with the function of appeals in the speech etiquette of the Kazakh and Tatar languages. In the Turkic languages, the system of using addresses is especially developed. They change depending on the level of acquaintance of the speaker, various social situations, the mood of the communicants, communicative and pragmatic goals. The speech etiquette of each people is closely connected with the traditions and national consciousness of this people. This can only be verified by analyzing the etiquette system of a given people. It is clear that the communication of people in society requires compliance with certain rules and norms of speech etiquette. It is especially important to observe the rules of etiquette when using appeals. Considering them as part of speech etiquette is a great opportunity, a real tool for studying the culture of the country. The study analyzes the features of the use of addresses of two languages ​​in some social situations. In the analysis of language units, the methods of functional-semantic analysis, collection and conclusion were used. As a result of the study, a large number of similar features of the use of forms of address in the Kazakh and Tatar language cultures were revealed. A comparative analysis shows that related terms are often used in the communication of strangers, and emotional vocabulary is actively used as addresses in the communication of close people. Key words: Kazakh language, Tatar language, speech etiquette, appeals, related terms.